Application Of Tomato Juice Therapy To Reduce Blood Pressure In Hypertension Patients Through The Application Of The Virginia Henderson Model At The Tresna Werdha Residence In Bengkulu City - Sela Nova Lestari A; Yance Hidayat (Utami Publisher, 2026)
Hypertension or high blood pressure is a condition when there is an increase in blood pressure, namely above 140 mmHg for systolic blood pressure and 90 mmHg for diastolic blood pressure. Systolic blood pressure is the blood pressure measured by a sphygmomanometer when the heart contracts so that it reaches the highest number, while diastolic blood pressure is the blood pressure measured when the heart expands so that the number is lowest (Yohanes, 2023). The general objective of this case study is to implement tomato juice therapy to reduce blood pressure in hypertensive patients through the application of the Virginia Henderson model at the Panti Tresna Werdha in Bengkulu City. This case study method is a descriptive method using a descriptive method, namely a method carried out with the main aim of creating a picture or description of a condition objectively and focusing on a particular object. The results of nursing care provided in cases of hypertension show an adaptive response in patients. These results prove that Virginia Henderson is effectively applied to hypertensive patients. Thus, the Virginia Henderson Theory can be considered as a method in providing quality nursing care. Virginia Henderson's theory, namely the Fulfillment of 14 Basic Human Needs, aims to make patients independent (Hernawan, 2018). Considering that some problems that can occur in hypertension sufferers can recur, Virginia Henderson's theory is an appropriate one.